The Meaning of Environmental Awareness Messages Signs through Film: Semiotic Analysis of Spirited Away Film - Vien Audrey (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Environmental awareness is an issue that has never ended until now, both in the natural environment, social environment, and artificial environment. Global warming and crime rates that continue to increase are clear evidence that there are still many people who are not aware of the critical role of humans in protecting the environment. The film "Spirited Away" is one of the Japanese animated films that discuss environmental issues and won various awards, one of which was the Oscar award. This study aimed to determine the denotative meaning, connotative meaning, and the myth of environmental awareness in the Spirited Away film. This research is qualitative research with an interpretative paradigm. The results of this study show that seven scenes have the meaning of environmental awareness, such as globalization, the loss of cultural identity, destruction of the natural environment, global warming, capitalism, and human morals. Hayao Miyazaki's Spirited Away is a work inspired by actual events that happened to him. This shows that this Japanese animation conveys a message based on the reality of human life that is packaged using a Japanese cultural approach that can be used as an example for the world of cinema, especially animation in Indonesia, to produce original works that have deep meaning.